Effects on the medical revenue of comprehensive pricing reform in Chinese urban public hospitals after removing drug markups: case of Nanjing. (3rd April 2018) - Tang, Wenxi; Xie, Jing; Lu, Yijuan; Liu, Qizhi; Malone, Daniel; Ma, Aixia
Abstract: Aims: The State Council of China requires that all urban public hospitals must eliminate drug markups by September 2017, and that hospital drugs must be sold at the purchase price. Nanjing-one of the first provincial capital cities to implement the reform—is studied to evaluate the effects of the comprehensive reform on drug prices in public hospitals, and to explore differential compensation plans. Methods: Sixteen hospitals were selected, and financial data were collected over the 48-month period before the reform and for 12 months after the reform. An analysis was carried out using a simple linear interrupted time series model. Results: The average difference ratio of drug surplus fell 13.39% after the reform, and the drug markups were basically eliminated. Revenue from medical services showed a net growth of 28.25%. The overall compensation received from government financial budget and medical service revenue growth was 103.69% for the loss from policy-permitted 15% markup sales, and 116.48% for the net loss. However, there were large differences in compensation levels at different hospitals, ranging from –21.92% to 413.74% by medical services revenue growth, causing the combined rate of both financial and service compensation to vary from 28.87–413.74%, There was a significant positive correlation between the services compensation rate and the proportion of medical service revenue ( p  < .001), and the compensation rate increased by 8% for every 1% increase in the proportion of services revenue. Discussion: Nanjing's pricing and compensation reform has basically achieved the policy targets of eliminating the drug markups, promoting the growth of medical services revenue, and adjusting the structure of medical revenue. However, the growth rate of service revenue of hospitals varied significantly from one another. Conclusions: Nanjing's reform represents successful pricing and compensation reform in Chinese urban public hospitals. It is recommended that a differentiated and dynamic compensation plan should be established in accordance with the revenue structure of different hospitals.